New insights in the diagnosis and treatment of equine piroplasmosis: pitfalls, idiosyncrasies, and myths - Mendoza, Francisco J.; Pérez-Écija, Alejandro; Kappmeyer, Lowell S.; Suarez, Carlos E.; Bastos, Reginaldo G. (Frontiers in Veterinary Science, 2024)
Equine piroplasmosis (EP) is a global tick-borne disease of equids caused by the intraerythrocytic apicomplexan parasites Theileria equi and Babesia caballi, and the more recently discovered Theileria haneyi. These parasites can be transmitted by several tick species, including Dermacentor, Hyalomma, and Rhipicephalus, but iatrogenic and vertical transmission are also common. Clinical signs of EP include poor performance, fever, icterus, abortions, among others, and peracute or acute forms of infection are associated with high mortality in non-endemic areas. EP is a reportable disease and represents an important barrier for the international trade of horses and other equids, causing disruption of international equine sports. Tick control measures, serological and molecular diagnostic methods, and parasiticidal drugs are currently used against EP, while vaccines remain unavailable. Since most acaricides used in equids are non-environmentally friendly and linked to drug resistances, this is considered as an unsustainable approach. Imidocarb dipropionate (ID) and buparvaquone (BPQ) are currently the main drugs used to control the disease. However, while ID has several side and toxic effects and recurrent failures of treatment have been reported, BPQ is less effective in the clearance of T. equi infection and not available in some countries. Thus, novel alternative and effective therapeutics are needed. While current trade regulations require testing equids for EP before exportation, the lack of standardized PCR tests and limitations of the currently recommended serological assays entail a risk of inaccurate diagnosis. Hereby, we propose a combination of standardized PCR-based techniques and improved serological tests to diminish the risks of exporting EP-infected animals making equid international trade safer. In addition, this review discusses, based on scientific evidence, several idiosyncrasies, pitfalls and myths associated with EP, and identifies weaknesses of current methods of control and gaps of research, as initial steps towards developing novel strategies leading to control this disease.